The State of Adaptation of Enterprises in Poland to the Paradigms of Industrial Production Industry 4.0 - Krystian Pawlowski (Communications of International Proceedings, 2020)
Industry 4.0 from the vision of the future has become a widely accepted reality for industrial companies, not only on a European but also worldwide scale. Taking into account the robotization rate, Poland is at the end of the European list with 42 robots out of 10 000 employees (data from 2019). However, the research conducted in 2018 shows that in the sector of micro, small and medium production enterprises located in Poland 60% of entrepreneurs have not heard about the concept of Industry 4.0 before. Therefore, a research problem was undertaken concerning the adjustment of Polish enterprises to the requirements of Industry 4.0, and in particular the adjustment to new paradigms of industrial production. The empirical research conducted in January 2020 covered 100 medium and large companies operating in Poland in various industries. This paper focuses on three issues related to the technological and business aspects of the digital transformation. The research covered the level of product agility, changes in manufacturing technology and the level of application of Lean Management methods and tools. The aim of the study is to determine the level of adjustment of enterprises in Poland to the requirements of industry 4.0 and to indicate whether the implementation of Lean Management methods and tools supports this adjustment.
Keywords: Industry 4.0; paradigms of industrial manufacturing; lean management; Cyber-Physical Systems; Internet of Things; Internet of Services; Smart Factory.